2021
DOI: 10.3390/ani11051272
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Clustering by Red Deer and Its Relevance for Management of Chronic Wasting Disease

Abstract: Herbivores like cervids usually graze on widely scattered forage, but anthropogenic food sources may cause spatial revisitation and aggregation, posing a risk for transmission of infectious diseases. In 2016, chronic wasting disease (CWD) was first detected in Norway. A legal regulation to ban supplemental feeding of cervids and to fence stored hay bales was implemented to lower aggregation of cervids. Knowledge of further patterns and causes of spatial revisitation can inform disease management. We used a rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Since it was first detected in 2016, and until December 2022, CWD has been detected in 18 moose, of which 11 were in Norway, 4 in Sweden and 3 in Finland, and also in 3 red deer in Norway (Table 7 ) (Mysterud et al., 2021c ). All cases in moose and red deer were of the Ly‐ phenotype.…”
Section: Assessment/resultsmentioning
confidence: 99%
“…Since it was first detected in 2016, and until December 2022, CWD has been detected in 18 moose, of which 11 were in Norway, 4 in Sweden and 3 in Finland, and also in 3 red deer in Norway (Table 7 ) (Mysterud et al., 2021c ). All cases in moose and red deer were of the Ly‐ phenotype.…”
Section: Assessment/resultsmentioning
confidence: 99%
“…This finding is consistent with a previous study from Wisconsin, USA that showed a decreasing prevalence of CWD among deer as the distance increased from a central CWD hotspot location (Joly et al., 2006 ). Sustained locally focussed culling within and as close as possible to L1 is a powerful management tool to complement CWD control measures such as limiting the movement of infected carcasses and live cervids by people; restricting baiting and feeding of deer, and increasing harvest rates via non‐selective culling (Mysterud et al., 2020 , 2021 ; Uehlinger et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The GPS collars recorded one position every 1 or 3 h. We removed data from the period of active culling of the herd (i.e., data after 10 August 2017). Red deer GPS data were available from 42 female (≥1 year old) and 9 male red deer (≥2 years old) marked during 2009-2012 (GPS collars manufactured by Followit) (Mysterud et al, 2012) and 2017-2019 (GPS collars manufactured by Vectronic) (Mysterud et al, 2021). Positions were taken every 1 h for females and every 2 h for males (from 1 September to 30 November).…”
Section: Gps Datamentioning
confidence: 99%